Depositional constraints and diagenetic pathways controlling petrophysics of Middle Miocene shallow-water carbonate reservoirs (Leitha limestones), Central Paratethys, Austria-Hungary. (March 2018) - Ali, Ahmed; Wagreich, Michael; Strasser, Michael
Abstract: Middle Miocene shallow-water limestones, the so-called Leitha limestones, comprise a widespread Middle Miocene lithological unit of the Central Paratethys Sea. It includes mainly limestones composed of corallinacean algae and other fossil debris and were deposited in shoals of various basins such as the Vienna, Eisenstadt-Sopron and Styrian basins of Austria where they form potential hydrocarbon reservoir rocks. Petrophysical parameters including porosity, permeability, density, P-wave velocity and magnetic susceptibility measurements were performed and evaluated. The sampled sites of Mannersdorf and Wöllersdorf quarries and drill-hole Bruckneudorf are located in the Vienna Basin and share the same principal limestones depositional facies that is massive, closely-packed rudstone facies. This facies has low porosities below 10%, low permeability lower than 1.2 mD except one samples at 68.5 mD, high bulk density of dry samples up to 2.64 g/cm 3 and high P-wave velocity up to 6761 m/s. In Mannersdorf, a second facies type of soft porous coarse-grained rudstone shows significantly higher porosity (up to 47%), higher permeability up to 124.3 mD, lower bulk density of dry samples less than 1.8 g/cm 3 and lower P-wave velocity less than 2798 m/s. This latter facies retains primary porosity and secondary porosity enhanced by dissolution. In contrast, the former facies type suffered intensive cementation, which destroyed the primary porosity, and in some cases, subsequent later dissolution and karstification enhanced secondary porosity partly. Kummer (Austria) and Fertőrákos (Hungary) quarries are located within the Eisenstadt-Sopron Basin. The well-sorted grainstone facies has high porosity up to 50%, extremely high permeability up to 31238 mD, low bulk density of dry samples less than 1.71 g/cm 3 and low P-wave velocity less than 3219 m/s. The poorly-sorted massive rudstone facies recorded only in Kummer quarry is less porous (porosities range from 22 to 31%) and less permeable. The role of dissolution predominates in these limestones besides compaction and pressure solution in the massive rudstone facies. Limestones from the Rosenberg quarry of the Styrian Basin show two facies types: (1) wackestone to packstone facies with lower porosity (up to 16.4%) and lower permeability ranges from 0.16 to 0.91 mD, compared to (2) the packstone facies with higher porosity (21%) and higher permeability of 1.83 mD. The influence of diagenesis on both facies is similar, represented by early marine cementation followed by partial dissolution and finally meteoric blocky cementation. The depositional influence on petrophysics of Leitha limestones, for instance, packing, sorting and grain size represents the basis for the differences in facies types in the same locality and among various localities. This depositional influence controls the subsequent stepwise diagenetic evolution the facies. Local depositional environments and their spatial evolution play a significant role on reservoir properties such as, at Mannersdorf the two facies types are varied due to the primary depositional characteristics and hence, the diagenetic evolution. Diagenetic pathways are principally similar in the different localities and basins; however, different stages of diagenesis are recorded due to different burial and exhumation histories. Highlights: The paper contains a description of the petrophysical parameters of Leitha limestones from different localities. These parameters are used to deduce the palaeoenvironmental and diagenetic characteristics of the rock unit. Leitha limestones from different basins display various depositional and diagenetic properties.